Bromatológical chemical study about the Aguamiel of Agave Americana L. (Maguey) - Bautista D., Nelson (2008)
PresentIy work was carried out the chemical bromatological study about the aguamiel of Agave americana L., the sample coming from the province Vilcashuarnan, department of Ayacucho (Perú). In this work it was also carried out preparation nectar of aguamiel with matter prime coming of the same province. In the chemist bromatological determination, the following results obtained expressed en g% of fresh sample: 87.38 of water content, 0.30 of totals proteins, 0.01 of ethereal extract, 12.03 of carbohydrates, 0.23 of ash, 0.05 of raw tibre, 0.97 of sugars directes reducers (g% glucose), Also, 9.08 of sugars totals reducers (g% glucose). And minerals expressed in mg%: 5.92 of sodium, 14.56 potassium, 8.60 of magnesium, 9.72 of calcium, 4.20 of phosphorum, 0.06 of iron, 0.07 of zinc and 0.03 of cupper. Also 14.82 mg% of vitamin C.